2006
DOI: 10.1097/01.brs.0000240203.98960.13
|View full text |Cite
|
Sign up to set email alerts
|

Wasting of Preoperatively Donated Autologous Blood in the Surgical Treatment of Adolescent Idiopathic Scoliosis

Abstract: The majority of PABD patients (51%) wasted minimum one autologous unit or were transfused at a high hematocrit (>30). More precise PABD guidelines are needed to limit unnecessary transfusion and wasted resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 25 publications
0
15
0
6
Order By: Relevance
“…Such options include patients positioning to avoid abdominal compression, hypotensive anesthesia, application of topical hemostatic agents to the decorticated bone, intra-operative cell salvage (ICS) system, acute normovolemic hemodilution, and administration of medications2,3,10).…”
Section: Introductionmentioning
confidence: 99%
“…Such options include patients positioning to avoid abdominal compression, hypotensive anesthesia, application of topical hemostatic agents to the decorticated bone, intra-operative cell salvage (ICS) system, acute normovolemic hemodilution, and administration of medications2,3,10).…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Autologous blood frequently goes unused and is wasted. 1 Finally, transfusion errors can occur and, despite PABD, patients are erroneously transfused with ALLO blood. Despite these negative features, PABD is still performed, due probably in part to physician and patient preferences to avoid ALLO blood exposure.…”
mentioning
confidence: 99%
“…One 2003 study analyzed the use of autologous pre-donated blood transfusion in surgery for scoliosis in 45 patients at one hospital in England. 23 The authors concluded that autologous blood transfusion required extra time, personnel, resources and cost £28.88 ($47.15 USD) per patient more than allogenic transfusion. 23 Additional concerns about unused autologous blood adding an unnecessary expense has been raised as well.…”
Section: Estimated Blood Volumementioning
confidence: 99%
“…23 The authors concluded that autologous blood transfusion required extra time, personnel, resources and cost £28.88 ($47.15 USD) per patient more than allogenic transfusion. 23 Additional concerns about unused autologous blood adding an unnecessary expense has been raised as well. 21,24 To date the cost of a unit of allogenic blood is variable and institution dependent.…”
Section: Estimated Blood Volumementioning
confidence: 99%